The impact of Cerdo, Marcion and Gnostic teachers on Roman Christianity in the second and third centuries - Löhr, Winrich Alfried (Early Christianity in Rome, 2026)
The following survey of our limited knowledge about Cerdo, Marcion and Gnostic Christian teachers and groups in second century Rome will not reconstruct the rich variety of their doctrinal positions but will instead focus on two questions: (1) What is the position of Marcion and various gnostic teachers with regard to, or within, or outside of - what you may call for want of a better word - "Christianity in second-century Rome"? (2) What is the continuing impact, or otherwise, of these Christian teachers on Roman Christianity in the second and third centuries?